Long‐term outcomes of real world 'watch and wait' data for rectal cancer after neoadjuvant chemoradiotherapy. (20th July 2020) - Simpson, G.; Hopley, P.; Wilson, J.; Day, N.; Haworth, A.; Montazeri, A.; Smith, D.; Titu, L.; Anderson, J.; Agbamu, D.; Walsh, C.
Abstract: Aim: A 'watch and wait' (W&W) strategy after neoadjuvant long‐course chemoradiotherapy (NACRT) remains controversial. Whilst encouraging short‐term data exist, the strategy will be judged on long‐term data. We present long‐term, real‐world UK data from a single National Health Service trust. Methods: An analysis was performed of a prospectively maintained W&W database over 9 years between 2010 and 2018. Outcome measures include incidence and time to regrowth and overall and disease‐free survival. Results: We diagnosed 563 rectal cancers in 9 years. In all, 283 patients underwent rectal resection (50.3%). NACRT was used in 155 patients for margin‐threatened tumours on staging MRI. Forty‐nine patients (31.6%) experienced either a 'near complete' or a complete clinical response (cCR) at their 10 weeks post‐NACRT assessment (MRI and endoscopy). The median age was 69 years (range 44–83), and the male to female ratio was 32:17. The median follow‐up was 38 months (range 12–96). The median tumour distance from the anal verge was 7 cm (1–15 cm). Twenty‐two patients had a cCR on initial assessment and 27 patients had a 'near' cCR. Of those 27 who experienced a 'near' cCR, 17 (63%) progressed to cCR on repeat assessment and 10 (37%) did not. Of these 10 patients, seven underwent standard surgical resection and three were unfit for surgery. R0 for the seven with delayed resection was 100%. Of 39 patients (22 cCR and 17 'near' cCR who progressed to cCR) (25.2% of those receiving NACRT), six patients experienced local regrowth (15.4%). The median time to local regrowth was 29 months (15–60 months). One of these six patients underwent salvage abdominoperineal resection, one was advised to have contact radiotherapy and four opted against surgery and also had contact radiotherapy. The overall survival was 100% at 2 years and 90% at 5 years. Disease‐free survival was 90.47% at 2 years and 74.8% at 5 years. Conclusion: A W&W treatment strategy was employed safely in this patient cohort with acceptable rates of local regrowth and survival.